Ekonomia jako nauka pozytywna. Refleksje na marginesie „Ekonomii dobra i zła” Tomáša Sedláčka - Dzionek-Kozłowska, Joanna (Annales. Etyka w Życiu Gospodarczym, 2013)
One of the fundamental methodological problems of economics as a separate science is the question whether economic theorists are able to restrict themselves to the description of facts without assessing them. Is it possible to create an economic theory utterly deprived of value judgements? In other words – is economics a positive science? This problem is still debatable, notwithstanding efforts to eradicate all value judgements from economic analysis and to treat it as a touchstone of the scientificity of economic reasoning. The main purpose of the article is to analyse Sedláček arguments and to confront his stance with other approaches. Furthermore, an attempt is made to assess whether his position could be attractive for contemporary mainstream economists.